Service Synergy: A Collaborative Approach within Libraries to Support Researchers’Information Literacy Skills - Stoeckel, Sheila (The 8th International Conference on Emerging Global Trends in University Library Development (ICEGTULD 2019), 2019)
Most university libraries have well-established information literacy instruction programs that collaborate with faculty to teach students the skills they need to be successful in today’s rapidly changing information age. However, approaches to providing information literacy support to faculty and professional researchers, has a propensity to be done through siloed initiatives or with individual subject specialist librarians. While the traditional research lifecycle model has gained wide acceptance, the myriad skills and resources needed to be successful at each step of the model, in addition to the rate at which research is changing, present challenges for many expert researchers and librarians. This paper will explore how collaboration among information literacy and researcher engagement librarians, investment in professional development, and campus networking can build a more programmatic approach to libraries providing campus researchers with the skills they need to be successful throughout their careers and thus elevate prestige for libraries along with their value to campuses worldwide.
Keywords: Research Subject Categories::SOCIAL SCIENCES::Other social sciences::Library and information science; information literacy; research services; collaboration